Effectiveness of Deep Cervical Flexor (DCF) Exercise on Neck Functional Scores in Helicopter Crew with Mechanical Neck Pain - Amalina, Nurika; Setiawati, Erna (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Mechanical neck pain is defined as neck pain due to biomechanical dysfunction in the neck or upper back. Exercise can reduce muscle tension and strengthen deep cervical flexor (DCF) muscles by helping to relieve pain. The prevalence of neck pain is considered high in helicopter crews compared to the general population. Aim: To investigate the effectiveness of DCF exercise on neck functional scores (study of helicopter crews with mechanical neck pain).Material and Methods: Experimental one pre and post-test group design. The samples were 14 squadron-31/serbu helicopter crew performing conventional DCF muscle exercise 12 times for 4 weeks with a frequency of 3 times each week. Neck function was assessed using the Neck Outcome Score (NOOS) which consists of domains of mobility, stiffness, symptoms, sleep disturbances, everyday activity and pain, participating in everyday life, and quality of life.Results: This study showed that the mean NOOS score before intervention was 30.64 (SD: 9.44) and the mean NOOS score after intervention was 8.57 (SD: 5.33). There was a significant difference in the NOOS score before and after deep cervical flexor exercise (p = 0.001).Conclusion: DCF exercises are effective for improving neck functionality in helicopter crew with mechanical neck pain.